OS 02-02 microRNA-204 AND SIRTUIN1 REGULATE VASCULAR ENDOPLASMIC RETICULUM STRESS AND ENDOTHELIUM-DEPENDENT VASORELAXATION. (September 2016) - Kassan, Modar; Vikram, Ajit; Li, Qiuxia; Kim, Young-Rae; Kumar, Santosh; Jacob, Julia; Kaikobad, Irani
Abstract : Objective: Endoplasmic reticulum (ER) stress leads to vascular endothelial dysfunction in hypertension. The role of microRNAs in vascular ER stress is not fully understood. Here we examined the role of vascular microRNA-204 (miR-204) in inducing endothelial ER stress and dysfunction by governing the expression of the SIRTUIN1 (SIRT1) lysine deacetylase. Design and Method: Human Umbilical Vein cells (HUVECs) were treated with tunicamycin or transfected with miR-204 Mimic or siRNA SIRT1. In other set of experiments, HUVEC cells were treated with tunicamycin and either transfected with miR-204 inhibitor or transfected with adenovirus of SIRT1. Expression of ER stress markers were determined by Western blots, RTPCR and Immunostaining in all these conditions. Additionally, we treated C57/b6 mice and endothelial specific knockout mice for SIRT1 with tunicamycin and we infused them with miR-204 inhibitor and we studied the vessels reactivity and the expression of ER stress markers. Results: miR-204 mimic decreased expression of SIRT1 and promoted ER stress in HUVECs. Tunicamycin induced endothelial ER stress was also mediated by miR-204. Moreover, knockdown of SIRT1 induced ER stress in HUVECs, which were rescued by a miR-204 antagomir. Tunicamycin-induced ER stress upregulated miR-204, and downregulated SIRT1 in HUVECs. Similarly and in endothelium of aortas and mesenteric arteries of mice, antagonism of miR-204, or SIRT1 overexpression, rescued endothelial cells from tunicamycin-induced ER stress. Similarly, antagonism of miR-204 in vivo with anti-miR-204 mitigated tunicamycin-induced vascular ER stress, decline in vascular SIRT1 and impairment of endothelium-dependent vasorelaxation. Moreover, tunicamycin-induced vascular ER stress and endothelial dysfunction were exacerbated in mice with conditional deletion of endothelial SIRT1. Finally, Vascular miR-204 was upregulated with high-fat diet feeding, anti-miR-204 prevented vascular ER stress stimulated by high-fat diet feeding. Conclusions: These findings show an important role for miR-204 as a mediator of vascular ER stress, and ER stress-induced endothelial dysfunction, via downregulation of endothelial SIRT1.